2011
DOI: 10.1007/s00425-011-1537-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deprivation results in photosynthetic hydrogen production in Chlamydomonas reinhardtii

Abstract: The unicellular green alga Chlamydomonas reinhardtii is able to use photosynthetically provided electrons for the production of molecular hydrogen by an [FeFe]-hydrogenase HYD1 accepting electrons from ferredoxin PetF. Despite the severe sensitivity of HYD1 towards oxygen, a sustained and relatively high photosynthetic hydrogen evolution capacity is established in C. reinhardtii cultures when deprived of sulfur. One of the major electron sources for proton reduction under this condition is the oxidation of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
86
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 85 publications
(174 reference statements)
1
86
0
Order By: Relevance
“…Photosynthetic yields decrease during N deprivation, even under phototrophic conditions where cells are entirely dependent upon photosynthesis (Philipps et al, 2012;Simionato et al, 2013). Chlorophyll (Chl) fluorescence, which is sensitive to environmental changes and stress conditions that induce alterations in photosynthetic components (Iwai et al, 2008), can monitor the efficiency of linear electron flow (Baker et al, 2007) and has indicated that in N. oceanica (Simionato et al, 2013) and other algae, including C. reinhardtii (Berges et al, 1996;Li et al, 2010;Blaby et al, 2013), photosynthetic efficiency falls after N deprivation.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Photosynthetic yields decrease during N deprivation, even under phototrophic conditions where cells are entirely dependent upon photosynthesis (Philipps et al, 2012;Simionato et al, 2013). Chlorophyll (Chl) fluorescence, which is sensitive to environmental changes and stress conditions that induce alterations in photosynthetic components (Iwai et al, 2008), can monitor the efficiency of linear electron flow (Baker et al, 2007) and has indicated that in N. oceanica (Simionato et al, 2013) and other algae, including C. reinhardtii (Berges et al, 1996;Li et al, 2010;Blaby et al, 2013), photosynthetic efficiency falls after N deprivation.…”
mentioning
confidence: 99%
“…The most abundant classes are the neutral lipids monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG) and the anionic lipids sulfoquinovosyldiacylglycerol (SQGD) and phosphatidylglycerol (PG; Frentzen, 2004;Shimojima et al, 2010;Mizusawa and Wada, 2012). Stress, nutrient deprivation, or changing environmental conditions cause changes in lipid composition, leading to effects on photosynthetic yield and efficiency (Li et al, 2012;Philipps et al, 2012). Cellular Chl and carotenoid concentrations provide additional measures of photosynthetic potential.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…S-deprivation reduced the photosynthetic O 2 -evolving machineries in the algal cells leading to intracellular anaerobiosis which would favour H 2 production. N-and P-deprivation that can also stimulate H 2 production, but with lower H 2 yields and longer induction time to reach an anoxic state 4,5 . Currently, green algae such as C. reinhardtii, Tetraspora sp.…”
Section: Introductionmentioning
confidence: 99%